Enhancing operational efficiency in peruvian textile SMEs: a case study of lean manufacturing implementation - Cabieses Chipoco, Andres (2025)
The textile industry is a major contributor to the global economy, particularly significant in Peru due to its rich history and traditional techniques. This sector not only provides substantial employment but also preserves cultural heritage and drives economic growth. Despite its importance, the Peruvian textile industry faces operational inefficiencies, particularly in machinery setup during product transitions, leading to high unproductive times and reduced outputs. Addressing these issues is critical for maintaining competitiveness and meeting industry standards. The proposed study introduced a Lean Manufacturing-based model to tackle these inefficiencies. The model integrated Systematic Layout Planning (SLP), 5S methodology, and Single-Minute Exchange of Die (SMED) techniques. SLP was employed to optimize plant layout, reducing transportation times and improving workflow. The 5S methodology aimed to create an organized and clean work environment, enhancing process stabilization. SMED focused on reducing machinery setup times, increasing production flexibility and responsiveness. The implementation of this model resulted in significant improvements. The Operational Efficiency Index increased from 83.4% to levels nearing the industry standard of 95%. Setup times were reduced by 49.80%, and transportation times between areas decreased by 53.81%. These improvements led to a notable economic impact, reducing annual losses and enhancing overall productivity and efficiency within the production process. Academically, this research contributed valuable insights into the application of Lean Manufacturing tools in the textile sector, a relatively underexplored area. Socioeconomically, the findings highlighted the potential for substantial gains in productivity and efficiency, promoting sustainable growth and competitiveness in the market. This study underscores the importance of continuous improvement and invites further exploration into innovative methodologies to enhance operational efficiency. Future research should focus on expanding the application of Lean tools and exploring their integration with Industry 4.0 technologies to further optimize textile production processes.